(untitled) (Medicine Today, 2019)
Introduction: Spinal anesthesia is used for 95% of planned cesarean sections in Bangladesh. It provides a fast and profound sensory and motor block. However, hypotension is a very common complication of spinal anesthesia during cesarean section, causing significant maternal and fetal morbidity and mortality. It could be associated with severe nausea, vomiting and even unconsciousness and pulmonary aspiration in the mother and for the baby hypoxia, acidosis and neurological injuries may result. Materials and Methods: This prospective randomized comparative study was conducted in the Department of Anesthesiology at Institute of Child and Mother Health (ICMH) from July 2017 to December 2017, on 110 adult pregnant women who underwent caesarean delivery. All study patients were randomly allocated into two groups. Group I (F group) patients received volume preloading with 15 ml/kg Ringer lactate solution before induction of spinal anesthesia and group II (E group) patients received IV ephedrine (5 mg in 1st minute after spinal anesthesia, 5 mg in 2nd minute and thereafter 1 mg in every minute for 15 minutes). Results: A statistically significant difference in the incidence of hypotension between group F (48%) and group E (24%) was found (p = 0.03). Regarding side effects, statistically significant (p = 0.23) incidence of nausea and vomiting was found in group F (20%) in comparison to group E (12%). Conclusion: We conclude that prophylactic IV ephedrine infusion is more effective than fluid preload to prevent spinal anesthesia-induced hypotension during caesarean section without causing significant tachycardia or hypertension. Medicine Today 2019 Vol.31(1): 39-41